Factors Affecting Corporate’s Coping Strategy Choice During The Covid-19 Outbreak: Case of Indonesia - Suhita Whini Setyahuni; Agus Triyani (Universitas Muhammadiyah Surakarta, 2021)
This study aims to investigate what factors determine the process of deciding coping strategies during the COVID-19 outbreak. The data analysis technique used in this study was multinomial logistic regression, using structured questionnaires as a data collection method. By analyzing 103 companies that participated in this survey, we found that financial performances and self-efficacy were determinant factors in selecting coping strategies. However, the perception of COVID-19 and the perception of government did not influence the coping strategy’s decision process.By adding a new perspective on entrepreneurial aspects and using the latest indicators of financial performances and perception on COVID-19 and government’ trust, this research contributes to the concept’ development of coping strategies decision making process. For business practice, our findings enrich knowledge on the types of coping strategies that managers can take during the COVID-19 outbreak. Our research offers worthwhile insight into the management accounting literature by providing empirical evidence, especially on the factors that drove the probability of coping strategies during the crisis